2016
DOI: 10.1177/0886260516675922
|View full text |Cite
|
Sign up to set email alerts
|

Mother Blame and the Just World Theory in Child Sexual Abuse Cases

Abstract: Mothers are blamed for a variety of negative experiences and outcomes of their children, including child sexual abuse (CSA). According to just world hypothesis (JWH), people have a need to view the world as one where there is no such thing as an innocent victim; that is, the world is fair and just. These beliefs predict victim blaming in situations such as sexual abuse, physical abuse, and robbery. However, JWH has not been applied to the examination of mother blame, a situation in which the blame target did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…For example, Maes' (e.g., Maes, 1998;Maes and Schmitt, 1999) distinction between ultimate justice and imminent justice seems promising, as blaming victims and offenders are related to imminent rather than long-term justice (Hafer and Sutton, 2016). Yet others suggested that BJW may be more complex than allowed for by self-report questionnaires (Toews et al, 2019). In light of the criticism regarding the construct and measurement of the BJW, our research findings indicate the need for further research, using other measures of BJW.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, Maes' (e.g., Maes, 1998;Maes and Schmitt, 1999) distinction between ultimate justice and imminent justice seems promising, as blaming victims and offenders are related to imminent rather than long-term justice (Hafer and Sutton, 2016). Yet others suggested that BJW may be more complex than allowed for by self-report questionnaires (Toews et al, 2019). In light of the criticism regarding the construct and measurement of the BJW, our research findings indicate the need for further research, using other measures of BJW.…”
Section: Discussionmentioning
confidence: 62%
“…Empirical research provides evidence of the just world hypothesis (JWH) in varied situations related to rape and sexual abuse. When individuals are faced with a threat to their BJW (i.e., no retribution for a crime), they are more likely to assert that the victim is to blame (e.g., Hayes et al, 2013;Landström et al, 2016;Toews et al, 2019). For example, Strömwall et al (2013) investigated the effects of BJW on blame attributions toward rape victims.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is also possible that unmeasured variables or perceptions of the participants regarding details not explicitly stated in the vignette influenced their disbursement of blame away from the father. For example, previous research on mothers has identified a number of variables influencing blame, including her prior relationship with the child (Toews et al, 2019) and whether or not the parent believes the child’s allegation of CSA or supports the child afterward (Elliott & Carnes, 2001). Believing is particularly salient in situations such as that depicted in the vignette where a close family member is the CSA perpetrator (i.e., it can be more difficult to believe a family member is capable of CSA; Elliott & Carnes, 2001), although it is important to note that Elliott and Carnes (2001) found that the majority of mothers do believe their child’s allegation of CSA, often within the first hour of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also identified education as being of importance to participants when assigning fault attributions, again for mothers. Toews and colleagues (2019) found that participants’ attributions were impacted by the education, or lack of education, about CSA that a mother gives to her child. Participants expressed the need for education to ensure that children know how to deal with sexual abuse because sexual abuse is common, if not expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation